Clinicopathologic features and BRCA mutations in primary fallopian tube cancer in Japanese women. (2nd July 2018) - Sakurada, Shoko; Watanabe, Yoh; Tokunaga, Hideki; Takahashi, Fumiaki; Yamada, Hidekazu; Takehara, Kazuhiro; Yaegashi, Nobuo
Abstract : In 26.7% of Japanese patients with primary fallopian tube cancer, BRCA mutations were found in the germline. Abstract: Objective: The present study aimed to clarify the clinicopathological features, including the level of p53 protein expression and BRCA mutations, of primary fallopian tube cancer (PFTC) in Japanese women. Methods: A multicenter clinical survey was conducted at three Japanese institutions. Clinical data in patients with PFTC between 1998 and 2016 were collected. Immunohistochemical staining of p53 and BRCA mutation analysis by exome sequence using paraffin-embedded surgical resected specimens were performed. Results: A total of 40 patients with PFTC were enrolled in the study. The median age was 58 years (range: 38–78 years); 31 patients were menopausal. Thirty-four (85.0%) patients were diagnosed with serous adenocarcinoma (high grade, 33; low grade, 1). PFTC was classified into ampulla type, fimbriae type and undeterminable type by tumor-occupying lesion; ampulla type and fimbriae type occurred with the same frequency. Among 30 patients with high-grade serous adenocarcinoma, 6 patients showed germline mutations of BRCA1 (stop-gain 4 and frameshift deletion 2) and 2 patients showed germline mutation of BRCA2 (stop-gain 1 and frameshift deletion 1). However, only 1 patient had familial history of breast or ovarian cancer. Patients with BRCA mutations in the germline were frequently observed in ampulla type and FIGO stage I/II cancers, but no significant difference in the frequency of p53 overexpression and overall survival was observed. Conclusions: Among Japanese patients with PFTC, 26.7% presented with BRCA mutations in the germline. Additionally, p53 was important for the carcinogenesis in fallopian tubes, independent of the specific BRCA mutation.